PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE CLASS CONCERN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII-4 MTsN LUBUK BUAYA PADANG - Safitri, Eka Maliana (Pendidikan Matematika, 2014)
This research is based on the students comprehension of mathematical concepts are still low. This is seen in the results of student learning classes VII MTsN Lubuk Buaya Padang in Academic Year 2014/2015. This study aims to determine whether students comprehension of mathematical concepts by applying active learning strategies Class Concern types with better than students comprehension of mathematical concepts with conventional learning in class VII MTsN Lubuk Buaya Padang. This was an experimental research which used research design Static Group Comparison. Sampling technique was done by purposive sampling, class VII-4 as experimental class and VII-3 as control class . The instrument of the research was a test of understanding mathematical concept. The test used is in the form of essay test with a reliability test was 0,749. The data gathered in this research was analyzed by using t test assisted. Results were obtained the result of the hypothesis test, it was known that P-value was 0,042 on the significance level 0.05 in which P-value < Î±. This result indicated that the mathematics conceptual understanding of the students taught by using Trading Places active learning strategy better than that of students taught by using conventional strategy was accepted.